2013
DOI: 10.1007/s12199-013-0334-x
|View full text |Cite
|
Sign up to set email alerts
|

Features of perceived neighborhood environment associated with daily walking time or habitual exercise: differences across gender, age, and employment status in a community–dwelling population of Japan

Abstract: Objective Perceived neighborhood environment (NE) is considered a determinant of daily physical activity (PA). However, evidence concerning differences among types of PA, gender, and age is limited. The study purpose was to clarify the association between NE and walking time (WT) or habitual exercise (HE) across gender, age, and employment status in a community-dwelling population of Japan. Methods A questionnaire mail survey with a stratified random 7,515 sampling was conducted in a northeast city in January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…All examined moderators of environment-PA associations were counted and summarised by the category of moderator tested. This included multiple factor (i.e., higher-order) moderating effects, tested formally (e.g., [ 59 ]) or not (e.g., [ 20 ]). Reporting higher-order moderating effects by moderator category resulted in findings being counted multiple times, i.e., once for each moderator category.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All examined moderators of environment-PA associations were counted and summarised by the category of moderator tested. This included multiple factor (i.e., higher-order) moderating effects, tested formally (e.g., [ 59 ]) or not (e.g., [ 20 ]). Reporting higher-order moderating effects by moderator category resulted in findings being counted multiple times, i.e., once for each moderator category.…”
Section: Methodsmentioning
confidence: 99%
“…Reporting higher-order moderating effects by moderator category resulted in findings being counted multiple times, i.e., once for each moderator category. For example, Chen and colleagues reported sex by employment status interactions, so the findings were reported twice, once under sex and once under employment status as moderators [ 20 ]. For this reason, the total number of moderating effects reported in this review is greater than the number of moderating effects reported in the articles.…”
Section: Methodsmentioning
confidence: 99%
“…To improve this generalizability and facilitate cross-national comparison, additional studies are therefore necessary beyond Western countries [ 12 , 13 ], particularly in Asian countries, where few studies have been reported. In Japan, researchers have recently reported on the association between perceived BE and PA [ 13 , 14 , 15 , 16 , 17 , 18 ], while a few others have objectively analyzed neighborhood environments in relation to PA [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a perspective of occupational prevention and health promotion, the approach presented in this study was aimed to integrate both objective parameters related to IAQ assessment and subjective perception of the environmental quality and safety. Previous studies investigated sport facilities focusing on single issues such as only questionnaires, or microclimate (Soares, 2015), personal information (Eime, 2013;Chen, 2013;Reimers, 2014), aptitude playing sport (Coledam, 2014;Laxer, 2013). Here we considered an integrated approach, to evaluate a possible multiple strategy to assess environmental quality in sport environments.…”
Section: Discussionmentioning
confidence: 99%
“…Sports facilities are complex and heterogeneous buildings and they are unique in their kind, for energy consumption, used materials, comfort requirements (Revel, 2014). Moreover, performing sport in healthy environments strengthens motivation in addition to other factors such as age, sex, socio-economic conditions, school, food habits, plant accessibility (Sani, 2012;Eime, 2013;Chen, 2013;Reimers, 2014;Coledam, 2014;Adlakha, 2015;Laxer, 2013).…”
Section: Introductionmentioning
confidence: 99%